Durable Acidic Oxygen Evolution Via Self-Construction of Iridium Oxide/Iridium-Tantalum Oxide Bi-Layer Nanostructure with Dynamic Replenishment of Active Sites - Guo, Qi; Li, Rui; Zhang, Yanan; Zhang, Qiqin; He, Yi; Li, Zhibin; Liu, Weihong; Liu, Xiongjun; Lu, Zhaoping (Nano-Micro Letters, 2025)
Proton exchange membrane (PEM) water electrolysis presents considerable advantages in green hydrogen production. Nevertheless, oxygen evolution reaction (OER) catalysts in PEM water electrolysis currently encounter several pressing challenges, including high noble metal loading, low mass activity, and inadequate durability, which impede their practical application and commercialization. Here we report a self-constructed layered catalyst for acidic OER by directly using an Ir–Ta-based metallic glass as the matrix, featuring a nanoporous IrO2 surface formed in situ on the amorphous IrTaOx nanostructure during OER. This distinctive architecture significantly enhances the accessibility and utilization of Ir, achieving a high mass activity of 1.06 A mgIr−1 at a 300 mV overpotential, 13.6 and 31.2 times greater than commercial Ir/C and IrO2, respectively. The catalyst also exhibits superb stability under industrial-relevant current densities in acid, indicating its potential for practical uses. Our analyses reveal that the coordinated nature of the surface-active Ir species is effectively modulated through electronic interaction between Ir and Ta, preventing them from rapidly evolving into high valence states and suppressing the lattice oxygen participation. Furthermore, the underlying IrTaOx dynamically replenishes the depletion of surface-active sites through inward crystallization and selective dissolution, thereby ensuring the catalyst’s long-term durability. Highlights: 1 A self-constructed catalyst with in situ formed IrO2/IrTaOx bi-layer nanostructure was fabricated for high-efficiency acidic oxygen evolution reaction by using an Ir–Ta-based metallic glass as the matrix. 2 The coordinated nature of the catalyst’s active site is manipulated through electronic interaction between Ir and Ta, resulting in superior activity and stability. 3 The underlying amorphous IrTaOx layer dynamically replenishes the depletion of surface Ir sites through inward crystallization and selective dissolution to ensure long-term durability.